2011
DOI: 10.2147/ibpc.s12215
|View full text |Cite
|
Sign up to set email alerts
|

Combining antihypertensive and antihyperlipidemic agents – optimizing cardiovascular risk factor management

Abstract: Clinical guidelines now recognize the importance of a multifactorial approach to managing cardiovascular (CV) risk. This idea was taken a step further with the concept of the Polypill™. There are, however, considerable patent, pharmacokinetic, pharmacodynamic, registration, and cost implications that will need to be overcome before the Polypill™ or other single-pill combinations of CV medications become widely available. However, a medication targeting blood pressure (BP) and lipids provides much of the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…[22][23][24][25][26] However various issues related to patents, drug interactions, regulatory restrictions, and financial aspects have to be addressed before such FDC medications will be freely available for clinical use. 7 Given the usual coexistence of hypertension and hyperlipidemia in cardiovascular disease, designing an FDC that combines drugs that lower BP as well as serum LDL-C offers a rational approach to managing these risk factors. To this end, one of the most tested combinations is that of amlodipine, an antihypertensive that acts by blocking calcium channels in the vascular smooth muscles, and atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26] However various issues related to patents, drug interactions, regulatory restrictions, and financial aspects have to be addressed before such FDC medications will be freely available for clinical use. 7 Given the usual coexistence of hypertension and hyperlipidemia in cardiovascular disease, designing an FDC that combines drugs that lower BP as well as serum LDL-C offers a rational approach to managing these risk factors. To this end, one of the most tested combinations is that of amlodipine, an antihypertensive that acts by blocking calcium channels in the vascular smooth muscles, and atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recent guidelines for the management of hypertension and hyperlipidemia, as recommended by the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure 2014 (JNC VIII) 5 and the American College of Cardiology/American Heart Association 2013 blood cholesterol guideline, 6 respectively, emphasize the overall assessment of BP and serum lipid levels in evaluating cardiovascular risk rather than assessment of each risk factor individually. 7 Presently, the drugs with a preferred mechanism of cardiovascular protection for antihypertensive therapy are those that inhibit the renin-angiotensin system (RAS). 8 Two classes of the drugs (the angiotensinconverting enzyme [ACE] inhibitors and the angiotensin II receptor blockers [ARBs]) have been discovered to have RAS inhibitory activity, albeit by different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Table (2) show the catalase activity, levels of TOS and TAS were significant decrease in G2 in levels of TOS and TAS when compared with G1. Also, a significant increase was found G2 compared with G1 in patient group.…”
Section: Resultsmentioning
confidence: 92%
“…Hyperlipidaemia is an increase in the lipids, and lipoproteins (1) . The combination of certain risk factors such as dyslipidemia can act multiplicatively or synergistically to increase the risk of atherosclerosis and heart disease (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, such conditions contribute to increasing the economic burden and affect the quality of life of the patients as the CV complications require angioplasty or coronary artery bypass graft surgery. In addition to this, in most cases, it has been observed that the patients having a long history of T2DM have been advised to take antihyperlipidaemic drugs such as statins to treat hyperlipidaemia as well as in many cases antihypertensives to treat hypertension (Zamorano 2011; Rosenblit 2016). Therefore, the dose-reduction of Gly 4.7-folds than the base value respectively (Prabhakar and Doble 2009).…”
Section: Introductionmentioning
confidence: 99%